Pengaruh Media Sosial Terhadap Perilaku Sosial Siswa - Nurul Aulia; Nurdiyana Nurdiyana; Sofyan Hadi (Indra institute Research & Publication, 2022)
Social media is an online media where users can easily interact with each other virtually, social media invites anyone who is interested to participate by giving feedback openly, commenting, and sharing information in a fast and unlimited time. It is undeniable that social media has a great influence in one's life. which has indirectly shaped a person's social behavior. However, for the community, especially teenagers, social media has become an addiction that makes users go without opening social media, so they are too comfortable and forget their essence as social beings who must interact directly with the surrounding environment, this has resulted in the community, especially teenagers, having a negative nature. apathetic towards the environment, and creating a young generation that grows into individuals with poor social behavior